2016
DOI: 10.1002/lary.26133
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Hearing Eight Years After Sudden Sensorineural Hearing Loss

Abstract: 4 Laryngoscope, 127:927-931, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 24 publications
1
39
0
1
Order By: Relevance
“…Historically, the consequences of monaural auditory deprivation have not been given much attention, as they were believed to be minimal. However, more recent studies have revealed that the effect of unilateral hearing loss (UHL) and single-sided deafness (SSD)on processing of auditory stimuli may have far reaching consequences affecting quality of life (QoL) (Harkonen et al, 2017) as well as educational outcomes and listening effort (Lewis et al, 2016). It may also affect language development in children (Anne et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the consequences of monaural auditory deprivation have not been given much attention, as they were believed to be minimal. However, more recent studies have revealed that the effect of unilateral hearing loss (UHL) and single-sided deafness (SSD)on processing of auditory stimuli may have far reaching consequences affecting quality of life (QoL) (Harkonen et al, 2017) as well as educational outcomes and listening effort (Lewis et al, 2016). It may also affect language development in children (Anne et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The mainstay of treatment options for idiopathic SSNHL include oral steroids, intratympanic steroid injections or a combination of both. 5 The National Institute for Health and Care Excellence, in their recent guidelines on hearing loss (NG98), highlighted the paucity of evidence assessing the comparative effectiveness of these treatments and issued a high priority research recommendation to identify the most effective route of administration of steroids as a first-line treatment for idiopathic SSNHL. 10 The National Institute for Health Research (NIHR) Health Technology Assessment Programme has since released a commissioned call for a trial to address this question.…”
Section: Withmentioning
confidence: 99%
“…In 71%-90% of cases, the cause is unknown despite investigation, and these cases are termed idiopathic SSNHL. 3 4 Idiopathic SSNHL is a serious condition, adversely impacting people's lives 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socially, the lack of understanding and perception of speech lead to social isolation and a decline in communication. With the sudden lifestyle change, many patients suffer from depression, and even those who recover experience debilitating anxiety that the hearing loss will reoccur [ 7 , 9 , 20 ].…”
Section: Introductionmentioning
confidence: 99%